Design and Optimization of CsPbI3 Perovskite Solar Cells Using SCAPS-1D - Muhamad Kevin Ristiansyah; Bayu Prasetya; Mochammad Ghulam Isaq Khan; Muhammad Yasin Siregar; Abyan Abdillah Saoloan Panjaitan; Eri Widianto; Eka Nurfani (Green and Sustainable Materials Society, 2026)
This study investigates the optimization of CsPbI3-based perovskite solar cells using SCAPS-1D simulation with a device structure of FTO/ZnO/CsPbI3/Spiro-OMeTAD/metal. Key parameters, including absorber thickness, defect density, acceptor concentration, and transport layer properties, were systematically analyzed. The results show that absorber thickness significantly affects device performance, with an optimal thickness of 1.6 μm yielding an efficiency of 17.66%. Optimization of defect density and acceptor concentration further enhances device performance. After overall optimization, the power conversion efficiency increases from 16.3% to 23.1%, with *V*oc improving from 1.19 V to 1.39 V, *J*sc from 18.33 to 20.5 mA/cm2, and FF from 75.2% to 87.4%. The improvement is supported by enhanced J–V characteristics and near-unity quantum efficiency over a wide wavelength range. These results demonstrate that parameter optimization plays a crucial role in achieving high-performance CsPbI3 perovskite solar cells.